Donald Trump, "Judeo-Christian Values," and the "Clash of Civilizations" - Haynes, Jeffrey (The review of faith & international affairs, 2017)
Anti-Muslim feeling in the USA reflects not only long-standing antipathy linked to the events of 11 September 2001 but also reveals the success of an ideologically-focused political argument, one that has deliberately exaggerated the extent of values-based incompatibility between all Muslims and all "Westerners." This was exhibited by Donald Trump and other leading Republicans in the 2016 presidential campaign, who sought to highlight the perceived virtues of American "Judeo-Christianity" while implicitly or explicitly denigrating the values and ethics of Muslims, both in America and around the world. The article examines the Trump administration's policy regarding America's claimed "Judeo-Christian values" and differences with those of Muslim-majority societies.